James B. Gardner and Paula Hamilton, eds., The Oxford Handbook of Public History - Salvanou, Emilia (Historein, 2020)
Review of James B. Gardner and Paula Hamilton, eds., The Oxford Handbook of Public History. Oxford: Oxford University Press, 2017. 568 pp.